First indigenous transmission of Japanese Encephalitis in urban areas of National Capital Territory of Delhi, India. Issue 6 (20th May 2013) - Kumari, Roop; Kumar, Kaushal; Rawat, Ashok; Singh, GirRaj; Yadav, Narendra K.; Chauhan, Lakhbir S.
Abstract Objective Until 2010, no Japanese encephalitis (JE) had been reported from Delhi. Upon report of four confirmed cases of JE in September 2011, detailed investigations were carried out to determine whether the cases were imported or indigenous. Methods Entomological surveys were carried out and all mosquito pools were tested for the detection of JE virus by ELISA method using specific monoclonal antibody. Human blood samples from contacts of the patients were tested by IgM‐captured ELISA method. Pig's blood samples were also tested for the detection of JE virus. Results Culex tritaeniorhynchus, Culex vishnui and Culex pseudovishnui mosquitoes were found. In contrast to rural areas, their breeding habitats were different in the city. 19 pools were tested. JE virus was detected in two pools of Cx. tritaeniorhynchus females reared from field‐collected larvae, indicating vertical transmission. One pool of Cx. vishnui was also positive. This is the first report for the detection of JE virus in mosquitoes from Delhi. JE IgM antibodies in five contacts/residents indicate recent infection. JE virus was also detected in pigs. Conclusion Present analysis shows that of four reported JE cases, three were confirmed indigenous, indicating that the virus is multiplying in the city. Mapping of infected JE vector mosquitoes in the cities is required for preventive measures to contain further spread of the disease.